FREQUENCY AND ASSOCIATIONS OF MARCUS GUNN PHENOMENON IN CONGENITAL PTOSIS - Maqsood Ahmad; Hafiza Sadia Imtiaz; Usama Iqbal; Muhammad Sharjeel; Syed Imad Zahir; Ibrar Hussain (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the frequency and various associations of Marcus Gunn Phenomenon in patients of congenital ptosis.